ANALISIS PERMINTAAN KREDIT KONSUMSI PADA BANK UMUM DI KALIMANTAN BARAT TAHUN 2004-2011 - B01107042, M.Faisal Fadli (Jurnal Pembangunan dan Pemerataan, 2013)
In writing this thesis conducted research goal is to investigate and analyze the effect of interest rates, inflation and GDP expenditure on the development of consumer credit demand and to identify and analyze a variable interest rate, inflation, and GDP expenditure which predominantly affects the demand for consumer credit in the Bank common in West Kalimantan. In writing this thesis research is the method through quantitative methods associative clause approach using secondary data, in this case should also be pointed out that supporting data for analysis in this paper is a data-quarter of the period 2004.1 - 2011.4. The analysis technique used is multiple regression, while the statistical test using t-test to test the effect of variable and partially f trials to test the effect of variables simultaneously with a significant level of 5%. Based on the research results that inflation has a negative direction and significant effect on demand for consumer credit, while GDP and interest rates have a positive direction and significant effect on the demand for consumer loans of commercial banks in West Kalimantan. The results of the calculations, the F test showed that Fhit> F table is equal to 489.7728> 2.95 which means that GDP by expenditure, inflation, and interest rates jointly significant effect on the value of consumer credit demand in West Kalimantan. In the results of t-test results obtained expenditure GDP, interest rates and inflation have significant real and close to the demand for credit. With the amount of consumer credit demand on the investment loan, it is expected that the government can encourage people to be more entrepreneurial in order to create a lifestyle that is accelerating the development goals established an independent society can be achieved. To create value lower demand for consumer loans that it must be done within the limits of the type of policies the funds raised by banks, especially banks. With the funds raised limits to restrict bank funds short term. So that economic activity is not limited to the act of consumption but the new investment activity. Key Word : Demand consumer credit, GDP by expenditure, Inflation, Interest Rate